Highly Efficient Solar Hydrogen Generation—An Integrated Concept Joining III–V Solar Cells with PEM1 Electrolysis Cells. Issue 1 (January 2014) - Rau, Sebastian; Vierrath, Severin; Ohlmann, Jens; Fallisch, Arne; Lackner, David; Dimroth, Frank; Smolinka, Tom
Abstract In this work, a concept of highly efficient solar–hydrogen generation by direct coupling of III–V multijunction solar cells with proton exchange membrane (PEM) electrolysis cells is presented. III–V solar cells under concentrated illumination feature voltages above 2 V enabling the generation of hydrogen by water electrolysis. The resulting "hydrogen concentrator" is called HyCon. The temperature‐dependent electrochemical behavior of a PEM electrolysis cell is analyzed and its current–voltage characteristics are presented. The distribution of the velocity of the water flow and pressure for different flow fields is simulated by fluidic simulation. An electrolysis cell featuring a porous fiber as a current collector without any flow‐field pattern shows no visible difference in performance compared to a cell with a flow field pattern. Outdoor measurements of a HyCon module with 6 cells show a maximum efficiency of 16.8 % for one of the HyCon cells. Higher currents at lower voltages are desirable. In this respect the III–V multijunction solar cells can be optimized to obtain a higher current by adapting the indium content of each sub cell. This will lead to an increase of the system efficiency. The improvements, which will be applied in the near future, are discussed.